The Curious Case Of 2½ D - Tobler, Waldo (Quaestiones Geographicae, 2015)
Some geographical phenomena are continuous and exist in whole number dimensions. Topography, for example. Other phenomena, such as population density, depend heavily on the area used in their computation. Some refer to this as existing in 2½ dimensions. Is the difference just because it is a computed, rather than an observed quantity? I argue the case for considering treatment of discrete geographic data as continuous.